ANALISIS PENDAPATAN HOME INDUSTRI USAHA BATIK TULIS DI KECAMATAN TANJUNGBUMI KABUPATEN BANGKALAN - Romadhon Triadi; Dwi Susilowati; Syamsul Hadi (Program Studi Ekonomi Pembangunan, 2018)
The objective of this research is to know the Net income, characteristic and the efficiency of home industry batik tulis in Tanjungbumi district Bangkalan regency. The instrument of this research is uses micro approach by π = TR-TC and E = TR / TC formulas. The result of this research shows the gross income that is got by home industry Batik about Rp. 128.500.000 a month, the lowest gross income is about Rp. 51.250.000 a month, and the average of the gross income is about Rp. 87.597.500 a month, meanwhile the net income is about Rp. 45.018.000 a month, the lowest net income is about Rp. 15.600.500 and the average of the income is about Rp. 31.926.578 a month. It shows that the income home industry batik in Tanjungbumi dstrict Bangkalan regency is profitable and efficient.Keyword : Efficiency, Home Industry, Net Income, Gross Income